An Analysis of Contextual Meaning on Michael Bube’s Song Lyrics - Mamun, Dafriana; Suastini, Ni Wayan; Ariyaningsih, Ni Nyoman Deni (Austronesian: Journal of Language Science & Literature, 2024)
This study aims to explain the contextual meaning found in the lyrics of Michael Buble using the theory of Lyons (1995) and to explain the context of the situation to support the analysis of meaning in the lyrics of Michael Buble using the theory by Halliday and Hasan (1985). This research uses a descriptive qualitative method. The result showed there are four contextual meanings found; these contextual meanings grouped in 2 or (50%) words, 1 or (25%) phrases, and 1 or (25%) clauses. The e contextual meaning consists of informal language and figurative language, which is analyzed based on the context of the situation, showing that the field or the topic of each song is about love between young adults, Michael Buble, and her story about love and her child. The tenor of the participant of each song has similarities using figurative language, idioms, and informal language. The mode of each song is the same in that all of them are written text but can be read if those songs are sung.